2019
DOI: 10.1101/792804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human GBP1 differentially targetsSalmonellaandToxoplasmato license recognition of microbial ligands and caspase-mediated death

Abstract: Human guanylate binding proteins (GBPs), a family of IFNγ-inducible GTPases, promote cell-intrinsic defence against pathogens and host cell death. We previously identified GBP1 as a mediator of cell death of human macrophages infected with Toxoplasma gondii (Tg) or Salmonella Typhimurium (STm). How GBP1 targets microbes for AIM2 activation during Tg infection and caspase-4 during STm infection remains unclear. Here, using correlative light and electron microscopy and EdU labelling of Tg-DNA, we reveal that GBP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 122 publications
(63 reference statements)
1
10
0
Order By: Relevance
“…6 ; ). Consistent with this, and reports of vacuole breakage in human macrophages ( Fisch et al, 2020 preprint), FIB SEM also captured incomplete vacuole membranes around type I tachyzoites within a macrophage ( Fig. 7 ; ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…6 ; ). Consistent with this, and reports of vacuole breakage in human macrophages ( Fisch et al, 2020 preprint), FIB SEM also captured incomplete vacuole membranes around type I tachyzoites within a macrophage ( Fig. 7 ; ).…”
Section: Resultssupporting
confidence: 88%
“…Using ssTEM and FIB SEM, we observed incomplete PV membrane in zebrafish brain cells and macrophages. PV breakage has been observed in vitro after IFN-γ stimulation of murine cells and human macrophages, and is thought to be part of the cell-intrinsic host defense mechanism against Toxoplasma tachyzoites ( Martens et al, 2005 ; Zhao et al, 2008 ; Yamamoto et al, 2012 ; Selleck et al, 2015 ; Fisch et al, 2020 preprint). Zebrafish possess an ortholog of IFN-γ together with a related gene (IFN-γ-rel), and studies have suggested that zebrafish IFN-γ (also known as Ifng1) expression is associated with host protection against bacterial infection, while IFN-γ-rel expression is associated with host protection against viral challenge ( Igawa et al, 2006 ; López-Muñoz et al, 2009 , 2011 ; Sieger et al, 2009 ; Yoon et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, antibodies specific for the inner core/ lipid A portion of LPS are able to bind to GBP1-coated but not uncoated bacteria in vitro, albeit not very efficiently[31]. These in vitro findings thus provide a molecular explanation for observations made by numerous research groups reporting the GBP1-dependent recruitment of the cytosolic lipid A sensor caspase-4 to the surface of the gram-negative bacteria S. flexneri and Salmonella enterica Thyphimurium in the host cell cytosol[31,32,63,83,84].Caspase-4 binds directly to lipid A via its caspase activation and recruitment domain (CARD)[85][86][87]. LPS or lipid A aggregates promote caspase-4 oligomerization via homotypic CARD interaction and lead to the induction of pyroptotic cell death through the proteolytic cleavage and activation of the pore-forming protein gasdermin D (GSDMD)…”
mentioning
confidence: 51%
“…GBP-dependent microbial lysis results in the release of pathogen-associated molecular patterns (PAMPs) including microbial DNA, which is sensed by the pattern recognition receptor absent in melanoma 2 (AIM2) in response to F. novicida or Toxoplasma gondii infections ( Figure 5A). Accordingly, AIM2-dependent induction of host cell death by F. novicida or the protozoan Toxoplasma is alleviated inside GBP-deficient cells [12,14,83,84,97].…”
Section: Gbps Promote Canonical Inflammasome Activationmentioning
confidence: 99%
See 1 more Smart Citation